High prevalence of Helicobacter pylori mixed infections identified by multilocus sequence typing in Ningbo, China - Zhang, Yongxiong; Gu, Haiying; Shi, Zhouhong; Chen, Weiqin; Li, Airu; Ye, Weiwei; Zhang, Cheng; Yuan, Huikun; Zhao, Mingming (Frontiers in Microbiology, 2023)
This study used multilocus sequence typing (MLST) to investigate the prevalence of H. pylori mixed infections and H. pylori mixed infections involving unrelated strains; and determined the phylogeographic groups of H. pylori recovered from patients in Ningbo, China. A total of 156 H. pylori isolates were obtained from a convenience sample of 33 patients with culture-positive H. pylori infection. MLST was used to classify 150 H. pylori clinical isolates and 12 methodological control strains (6 clinical isolates and 6 strains of American Type Culture Collection H. pylori) into 43 and 12 sequence types (STs), respectively. In this study, 246 new alleles and 53 new STs were identified by MLST. The prevalence of mixed infections was 41% (11/27). The prevalence of H. pylori mixed infections involving unrelated strains was 46% (5/11) and the prevalence of H. pylori mixed infections involving completely unrelated strains (strains with all 7 housekeeping genes different) was 36% (4/11). A phylogenetic tree was created to determine the evolutionary relationships between different strains. The STs in this study were clustered within the hspEAsia subgroup (98%) and hpEurope group (2%). H. pylori mixed infections were common in Ningbo, China. The H. pylori isolates belonging to the hpEurope group were recovered from three different biopsy samples in a native Chinese patient. Most of H. pylori strains colonizing the antrum, corpus, and duodenum bulb were homologous.